EUTHYROID GRAVES’ OPHTHALMOPATHY WITH NEGATIVE TSH RECEPTOR ANTIBODY (TRAB) IN 2 FILIPINO MALES - Santos, Maria Regina; Jasul Jr., Gabriel; Bautista, Francesca Paula (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Graves’ ophthalmopathy (GO) frequently occurs among female hyperthyroid patients. Commonly, they are positive for thyroid autoantibodies, as part of GO’s pathogenesis. The occurrence of both euthyroidism and autoantibody negativity in GO can be a diagnostic dilemma. Below are 2 cases of euthyroid GO (EGO) among Filipino males with negative TRAb. CASE A 60-year-old diabetic male (poorly controlled) was admitted for a 2-week history of progressive left eye swelling, with pain and redness of the periorbital area, but with no fever. He was already treated with antibiotics but to no avail. He had history of EGO, but was already in remission for the past years. Examination revealed left eye swelling and erythema, which was warm, firm, and tender. Another 45-year-old male was seen in the OPD for a 5-year history of bilateral proptosis with no other symptoms. On examination, eyelids were noted to be swollen and nonerythematous. Orbital CT scans of both patients showed bilateral proptosis, with no orbital mass, with thickening of extraocular muscles, suggestive of thyroid-associated orbitopathy. TRAb levels were negative for both patients. Both were also biochemically and clinically euthyroid, and responded well to steroids and supportive measures. CONCLUSION GO can occur even in biochemically and clinically euthyroid males, though lesser in frequency (0.02-1.10/10,000 population). TRAb may also be negative, which may be due to assay sensitivity or intrathyroidal TRAb. In addition, imaging studies (CT and MRI) should be emphasized as an important part of diagnostic examinations.